Transformation of POLRI's Leadership Style in Managing the Unique Potential of Gen Z Personnel as a Foundation for Building a Positive Image of Traffic Police Accepted by the Public - Pramesti, Shinta Ayu; Setiono, Joko; Anggoro, Purwadi Wahyu (Jurnal Greenation Sosial dan Politik, 2025)
The transformation of leadership styles within the Indonesian National Police (Polri) has become a strategic necessity amidst the growing dominance of personnel from Generation Z. This generation brings distinct characteristics from their predecessors, such as openness to technology, a preference for collaborative work patterns, and expectations for participatory and meaningful leadership. Meanwhile, Polri's traditional leadership style remains rooted in hierarchical, one-way command structures, often clashing with the expectations of Gen Z personnel. In the context of Traffic Police (Polantas), the successful management of this generation’s human resources has a direct impact on public perception and the institutional image. This study uses a normative juridical method with a conceptual approach and analysis of the latest regulations, such as Law No. 2 of 2002 on the National Police, Polri Regulation No. 7 of 2022 on the Police Professional Code of Ethics and its Commission, and the Ministry of Administrative and Bureaucratic Reform Regulation No. 6 of 2022 on ASN Performance Management. The findings indicate that an adaptive leadership style grounded in values, technology, and two-way communication can address internal challenges while enhancing the image of Polantas as professional, humanistic, and transparent. Optimizing Gen Z’s potential within Polri’s organizational structure -especially in public service units like Polantas- requires organizational culture transformation, contextual training, and an accountable performance management system. The synergy between internal development and public participation is key to achieving long-term success in this transformation.